Facade, Grand Hotel - Ghosh, Ayan (2023)
The Grand Hotel has ground-level windows with outward projecting canopies painted in alternating bands of blue and white. Above the windows, bracketed cornice runs all around the building, supporting balconies on the first floor (also on the third-floor level). The second-floor balconies are supported by stone brackets.